Japanese encephalitis in children - Nurhayati Masloman; H S Widarso; W Cicilia (Paediatrica Indonesiana, 2005)
Japanese encephalitis is a zoonotic disease causedby Japanese encephalitis virus, attacking domesticanimals, mainly pigs and birds. It is transmittedto humans by mosquito bites, namely Culextritaeniorhyncus.